Two-dimensional frameworks formed by pentagonal bipyramidal cobalt(ii) ions and hexacyanometallates: antiferromagnetic ordering, metamagnetism and slow magnetic relaxation. Issue 28 (29th June 2017) - Shao, Dong; Zhou, Yan; Pi, Qian; Shen, Fu-Xing; Yang, Si-Run; Zhang, Shao-Liang; Wang, Xin-Yi
Abstract : Two-dimensional frameworks constructed by pentagonal bipyramidal Co II and [M(CN)6 ] 3− units have been synthesized and characterized structurally and magnetically. Abstract : We herein report the syntheses, structures, and magnetic properties of two isostructural two-dimensional (2D) coordination polymers based on a pentagonal bipyramidal Co II unit [Co(TODA)] 2+ and two hexacyanometallates, namely [M III (CN)6 ]2 [Co II (TODA)]3 ·9H2 O (M = Cr (1 ), Co (2 ), TODA = 1, 4, 10-trioxa-7, 13-diazacyclopentadecane). Structure analyses show that both complexes have 2D honeycomb structures where the [Co(TODA)] 2+ units are bridged by the [M III (CN)6 ] 3− groups through three cyano groups in the facial positions. Magnetic investigation reveals ferromagnetic coupling between the Cr III and Co II centres through cyanides in1 . Due to the antiferromagnetic interaction between the layers, compound1 exhibits an antiferromagnetic ordering below 11.4 K, and shows a metamagnetic phase transition under an external dc field. Due to the disorder of the TODA ligands, compound1 shows a spin glass behavior, which leads to slow magnetic relaxation in1 . A butterfly-shaped hysteresis loop at 1.8 K can be observed with a coercive field of 720 Oe, which is quite large for cyano-bridged Cr–Co molecular magnets. For compound2 containing the diamagnetic [Co III (CN)6 ] 3− unit, field-induced slow magnetic relaxation was also verified, which makes compound2 a rare example of an SIM assembled in a 2D network. An easy-plane magnetic anisotropy with a positive D value (29.9 cm −1 by PHI and 26.5 cm −1 by Anisofit2.0) was deduced for hepta-coordinated Co II centers. These results show the efficiency of the strategy of combining cyanometallates and pentagonal bipyramidal precursors for novel molecular magnetic materials.